HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG TRIAGE DENGAN PENERAPAN TRIAGE DI IGD RUMAH SAKIT UMUM DAERAH PATUT PATUH PATJU KABUPATEN LOMBOK BARAT - Antoni Eka Fajar Maulana (Jurnal PRIMA, 2017)
Triage is a selection system and the selection of patients to ensure the urgency level and the priority to give the treatment to the patients. Based on the data, there are 18 nurses in IGD Rumah Sakit Umum Daerah Patut Patuh Patju West Lombok Regency. The results of the initial observation in IGD Rumah Sakit Umum Daerah Patut Patuh Patju West Lombok regency shows that the initial treatment processdid not include the triage process, for example the patients get the treatment directly without determining the level of the urgency first. In this study, the researcher used descriptive correlational design. The population and the sample of this study were all of the nurses in IGD Rumah Sakit Umum Daerah Patut Patuh Patju, West Lombok regency which amounts to 18 people. The instruments that are used in this study were observation sheet and questionnaire. The data analysis that is used in this study was chi-square with the significance level of 0,05%. In order to know the relation between the nurses’ knowledge of triage and the implementation of triage in IGD Rumah Sakit Umum Daerah Patut Patuh Patju West Lombok regency, the researcher used chi-square to analyse the data. Based on the data analysis, the results shows that the calculation of SPSS with the significance level of P value = 0,040 with the error level α= 0,05. Therefore, the P value is < nilai α (0,040 < 0,05). In conclusion, this study shows that there is a relation between the level of the nurses’ knowledge of triage and the application of triage in IGD Rumah Sakit Umum Daerah Patut Patuh Patju West Lombok regency. Therefore, from this study, the hospital can get the input to revise the standard procedure about triage in IGD Rumah Sakit Umum Daerah Patut Patuh Patju West Lombok Regency. Key words : Knowledge, Application